2017
DOI: 10.1016/j.plabm.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Fecal zonulin is elevated in Crohn’s disease and in cigarette smokers

Abstract: ObjectivesHuman zonulin is a protein that increases permeability in the epithelial layer of the small intestine by reversibly modulating the intercellular tight junctions. There is not sufficient information available about zonulin's participation in inflammatory bowel diseases (IBD). The aim of this study was therefore to investigate fecal and serum zonulin in IBD patients and its relation to the disease localization, behavior and smoking status.Design and methodsForty IBD patients and forty healthy persons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Current literature gives different values for stool zonulin concentrations. Malíčková et al [39], based on the recommendations of the ELISA manufacturer-OrgenTec, Germany, indicated normal zonulin concentrations of 61 ng/mL ± 46 ng/mL. On the other hand, the cut-off upper normal limit for adults given by Lamprecht et al was a zonulin concentration value of 30 ng/mL [40].…”
Section: Discussionmentioning
confidence: 99%
“…Current literature gives different values for stool zonulin concentrations. Malíčková et al [39], based on the recommendations of the ELISA manufacturer-OrgenTec, Germany, indicated normal zonulin concentrations of 61 ng/mL ± 46 ng/mL. On the other hand, the cut-off upper normal limit for adults given by Lamprecht et al was a zonulin concentration value of 30 ng/mL [40].…”
Section: Discussionmentioning
confidence: 99%
“…A widely studied inflammation-related biomarker called zonulin was found to be elevated in both faeces and serum during the active CD phase, but not in UC. 91 Another barrier-integrity-specific molecule is Rho-A, which was found to be downregulated in IBD 92 and Rho-associated kinase upregulated in inflamed mucosa of CD patients. 93 It was proved that these alterations are key mediators of chronic inflammation, cytoskeleton rearrangement and skewed cell shedding.…”
Section: Gut Barrier and Intestinal Permeability: Novel Targets For Cmentioning
confidence: 99%
“…Twenty‐four studies reported on 29 statistically significant biomarkers and association with altered IP . Two studies reported that fasting glucose had a weak positive correlation with IP (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies reported on 29 statistically significant biomarkers and association with altered IP. 10,23,25,32,35,[40][41][42][43][44][50][51][52][53][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Two studies reported that fasting glucose had a weak positive correlation with IP 44,53 (Table 5). Moreover, an additional study reported that a plasma glucose level >5.7 nmol/L is associated with a greater odds of having altered IP (OR = 2.09; 95% CI: 2.09, 4.18; P = 0.036) in the general population 23 (Table 3).…”
Section: Biomarker Risk Factorsmentioning
confidence: 99%